2016
DOI: 10.21608/jppp.2016.50142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Fertilization Doses of Cotton Crop Insects and Their Certain Associated Predators

Abstract: Field experiments were carried out at Sidi Salem District, Kafr El-Sheikh governorate to study the influence of two nitrogen rates in combination with phosphorus (P) and Potassium (K) at their balance rate N:P:K = by ratio of (67:30:24) and high (N) rate 1.5N:P:K by ratio of (100.5:30:24) on the population numbers of cotton aphids and whitefly (adults) infesting cotton crop in addition to some associated predators during tow seasons (2011 and 2012). Obtained results revealed that the population densities of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Cotton is highly nutrient intensive crop and requires a balanced nutrition. However, imbalanced fertilizer application, either excessive use of nitrogenous fertilizers or under nutrition in the fear of the whitefly and poor or improper application of phosphatic or potassic fertilizers is very common ( Saleh et al, 2016 ). Availability of alternative potential hosts during the season and off-season may have created favorable niche for this pest.…”
Section: Discussionmentioning
confidence: 99%
“…Cotton is highly nutrient intensive crop and requires a balanced nutrition. However, imbalanced fertilizer application, either excessive use of nitrogenous fertilizers or under nutrition in the fear of the whitefly and poor or improper application of phosphatic or potassic fertilizers is very common ( Saleh et al, 2016 ). Availability of alternative potential hosts during the season and off-season may have created favorable niche for this pest.…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that in both seasons, N 3 or N 2 contributed to a rise in whitefly populations relative to N 1 . Saleh et al (2016) found that whitefly rates were greater in soil that had received a high N fertilization.…”
Section: Mineral N Fertilizer Ratesmentioning
confidence: 95%
“…For example, some investigators have been studied the relationship between nitrogen fertilizer levels and the piercing-sucking insect pests as Abo-Zaid (2011) on kidney bean and Draz et al (2013) on tomato plants. Also, some investigators have been studied the effect of potassium fertilization levels on the piercing-sucking insect pests (Saleh et al 2016 andAwadalla et al, 2017a, b).…”
Section: Introductionmentioning
confidence: 99%